Acupoint stimulation, massage therapy and expressive writing for breast cancer: A systematic review and meta-analysis of randomized controlled trials. (August 2016) - Lee, Phoebe Lyssandra Tan; Tam, Ka-Wai; Yeh, Mei-Ling; Wu, Wei-Wen
Highlights: Acupoint stimulation has an effect for general pain and fatigue in middle-aged women with breast cancer. Massage therapy has an effect for anxiety in middle-aged women with breast cancer. Expressive writing has an effect for quality of life in middle-aged women with breast cancer. Non-conclusive results were found for sleep and depression. More conclusive outcomes may be achieved resulting upon successful shared decision-making. Abstract: Researches have accumulated using non-pharmacologic interventions including acupoint stimulation, massage therapy and expressive writing to manage breast cancer-related symptoms. Results from randomized controlled trials (RCTs) can get contradictory. Objective: A systematic review and meta-analysis were conducted to determine the effects on the quality of life, negative emotions and disease-related symptoms among women with breast cancer. Methods: Two independent researchers performed a structured search using data sources including MEDLINE, CINAHL, Cochrane Central Register of Controlled Trials, EMBASE, PubMed and PsychINFO from the beginning of time until the first week of January 2015. A total of 23 acupoint stimulation, massage therapy and expressive writing RCTs were included in the review. Results: The study showed that no single intervention could be put under the spotlight exhibiting an overall effective result on all measured outcomes; however, looking into each one in detail shows different results in specific outcomes. Among the three interventions, acupoint stimulation has a treatment effect for general pain (MD = −1.46, 95% CI = −2.38 to −0.53) and fatigue (MD = −2.22, 95% CI = −3.68 to −0.77), massage therapy has a treatment effect for anxiety (MD = −0.50, 95% CI = −0.77 to −0.24), and expressive writing has a treatment effect for quality of life (MD = 7.18, 95% CI = 0.38 to 13.98). The measurement other outcomes showed either ineffective or equivocal results. Conclusion: Non-pharmacologic interventions including acupoint stimulation, massage therapy and expressive writing have an effect on a middle-age woman with breast cancer. However, because of limitations, the seemingly promising results should be interpreted with caution.